2017
DOI: 10.16965/ijar.2017.132
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Common Origin of Lingual and Facial Artery From the External Carotid Artery

Abstract: Background: The common carotid arteries provide the major source of blood to the head and neck region. In the present study, we studied about the variation in the origin of lingual and facial artery and specifically, the linguofacial trunk. The knowledge of this anatomical variation is important in the surgeries of head, neck and face and also for the radiologists to understand and interpret carotid system imaging when undertaking cerebral angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…Both the lingual artery (LA) and facial artery (FA) take their origin from the ECA in 21 cases (84%) and 22 cases (88%), respectively, while sharing a common trunk called the linguofacial trunk in 8% of them in this present study. This is in agreement with a similar study done by Anuradha and Chitra [33] which found the prevalence of origins of both the LA and FA at the anteromedial surface of the ECA as a separate branch in 27 cases (90%) of the 30 cases and both sharing a common trunk as the linguofacial trunk in 10% of the cases. Likewise, Sanjeev et al [10] reported that the lingual artery was found to arise from the anteromedial surface of the external carotid artery as a separate branch in 78.38% (29/37) of the cases and shared a common trunk in 7 cases (18.92%) with the facial artery (linguofacial trunk).…”
Section: Eca In Relation To Its Branchessupporting
confidence: 93%
“…Both the lingual artery (LA) and facial artery (FA) take their origin from the ECA in 21 cases (84%) and 22 cases (88%), respectively, while sharing a common trunk called the linguofacial trunk in 8% of them in this present study. This is in agreement with a similar study done by Anuradha and Chitra [33] which found the prevalence of origins of both the LA and FA at the anteromedial surface of the ECA as a separate branch in 27 cases (90%) of the 30 cases and both sharing a common trunk as the linguofacial trunk in 10% of the cases. Likewise, Sanjeev et al [10] reported that the lingual artery was found to arise from the anteromedial surface of the external carotid artery as a separate branch in 78.38% (29/37) of the cases and shared a common trunk in 7 cases (18.92%) with the facial artery (linguofacial trunk).…”
Section: Eca In Relation To Its Branchessupporting
confidence: 93%
“…Because of this, the incidence of solitary LA is lower, in contrast to the majority of other studies which reported incidence between 77.1% and 90.0%. [20][21][22][23][24][25][26][27][28][29] The current finding is closer to the incidence of solitary LA observed in the Japanese. 30 The LFT is the most commonly observed LA variant, followed by the TLT variant.…”
Section: Discussionsupporting
confidence: 71%
“…Our findings were contrasted that from other populations (Tables 5 and 6) with some populations having higher values of the variations as compared to others. 13,1821…”
Section: Discussionmentioning
confidence: 99%